The impact of colostomy on the patient's life - Campos,Karis de (2017)
Abstract Purpose To evaluate the emotional, psychological, sexual, social, and professional impact, before and after surgery, on individuals submitted to a colostomy. Methods The study was carried out in two stages, with the participation of 15 individuals. First, we evaluated the emotional, psychic, sexual, social, and professional aspects of their lives, in the preoperative period of colostomy surgery. After that, the same aspects were evaluated six months after the surgery. This evaluation was based on the application of a questionnaire with 16 objective questions. Results Of the interviewees, 53.64% decreased their willingness to go out and do activities outside their homes, with a statistical significance of p = 0.001. Regarding the environment, 53.85% of the interviewees showed a perception of worsening of the environment. About physical activity, 66.65% showed a difference in the performance of physical activity after colostomy, being statistically significant, with p = 0.001. The sports environment did not change in 50% of the participants. Patient sexuality showed a significant decline with statistical significance (p = 0.008). Conclusion The impact that the colostomy generated on the patients’ lives, regarding the evaluated aspects, was perceptible, being of great importance the careful indication of this procedure to the patient.